Effects of fertilization measures on soil fertility and crop yields in drylands of the North China Plain: a meta-analysis - Chang, Yi; Zhang, Xianmei; Shu, Qing; Sun, Zihao; Yang, Mei; Liu, XiaoYan; Guo, Jinpeng; He, Zhenquan; Li, Ling; Huang, Jing; Zhi, Jinhu; Chen, Guodong; et al. (Frontiers in Plant Science, 2026)
This study aims to quantify the effects of three fertilization patterns—“chemical fertilizer alone,” “organic fertilizer alone,” and “mixed application of organic and inorganic fertilizers”—on soil fertility and crop yields. It also assesses the relationships among baseline soil properties, climatic factors, and fertilization effects in the North China Plain. By compiling relevant literature on these three fertilization patterns over the past 30 years in the region and employing meta-analysis methods, this study incorporated 63 wheat-related studies (1,065 datasets) and 34 maize-related studies (631 datasets). The analysis examined the effects of different fertilization methods on crop yield, soil nutrients, microbial carbon and nitrogen content, and soil enzyme activity, as well as the relationships between baseline soil properties, climatic factors, and fertilization outcomes. Results revealed: 1) Short-term application of chemical fertilizers and organic-inorganic composite fertilizers significantly increased wheat yields more than maize yields, whereas organic fertilizer application boosted maize yields more than wheat yields. Organic-inorganic composite fertilization most significantly enhanced soil microbial biomass and key soil enzyme activities, while chemical fertilizer alone showed the weakest improvement effects. 2) Fertilization impacts yield under baseline conditions of soil pH 6–8, soil organic matter content below 15 g/kg, annual mean temperature of 13°C–14°C, and annual precipitation exceeding 500 mm. 3) Long-term application of chemical fertilizers alone shows slowing yield increases, whereas organic-inorganic composite fertilization sustainably boosts yields and mitigates the impact of single factors on production. Unified comprehensive fertilization rates for wheat and maize are recommended as follows: nitrogen fertilizer application of 150–225 kg·ha⁻¹, phosphorus fertilizer of 60–90 kg·ha⁻¹, potassium fertilizer of 30–60 kg·ha⁻¹, supplemented with 7.5–9 tons·ha⁻¹ of organic fertilizer. This approach outperforms single-fertilizer regimes in improving soil microbial properties and enzyme activity, serving as the key to superior yield maintenance. The recommended integrated fertilization rates strike a balance between reducing chemical fertilizer use, stabilizing yields, and enhancing soil fertility, providing practical guidance for fertilizer management in the North China Plain.